Handbook of classroom management - Emmer, Edmund T, Ed; Sabornie, Edward J, Ed (Routeledge, 2015)
"The field of classroom management is not a neatly organized line of inquiry, but rather consists of many disparate topics and orientations that draw from multiple disciplines. Given the complex nature of the field, this comprehensive second edition of the handbook is an invaluable resource for those interested in understanding it. It provides the field with up-to-date summaries of research on the essential topics from the first edition, as well as fresh perspectives and chapters on new topics. It is the perfect tool for both graduate students and practitioners interested in a field both fascinating and not immediately accessible without the proper guidance"--